Work-life balance of homestay operators in Jammu and Kashmir - Ahmad Dar, Ajaz; Raina, Danish Iqbal; Ahmad Bhat, Sajad; Abdulla, Parvez (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This study investigates the work-life balance of homestay operators in Jammu and Kashmir, a region renowned for its cultural richness and natural beauty and heavily reliant on tourism for economic stability. As homestays grow in popularity, understanding the challenges faced by operators in balancing professional and personal responsibilities becomes critical. A qualitative approach using thematic analysis was adopted to identify key issues influencing work-life balance. In-depth interviews with 25 homestay operators provided rich insights into their lived experiences and coping strategies. The analysis identified themes such as excessive workload, family involvement, emotional stress, and the quest for autonomy. Operators face unique challenges due to seasonal demand fluctuations and cultural expectations. Effective coping mechanisms included setting boundaries, leveraging community support, and practicing time management. The findings emphasize the need for strategies that sustain the economic viability of homestays while safeguarding operator well-being. Policy recommendations include fostering supportive environments, providing mental health resources, and adopting flexible operational practices. These insights are crucial for tourism stakeholders, policymakers, and researchers aiming to enhance the quality of life for homestay operators and promote sustainable tourism in Jammu and Kashmir.